Unusual Presentation of Malignant Melanoma: A Case of Giant Amelanotic Involvement of the Hand - Gargarin Nabalah; Henky Agung Nugroho (HM Publisher, 2025)
Malignant melanoma, a cancer originating from melanocytes, typically presents as a pigmented lesion. Amelanotic melanoma, a subtype lacking pigmentation, poses diagnostic challenges due to its varied clinical appearance. Acral amelanotic melanoma (AAM), occurring on the palms, soles, and subungual areas, is particularly rare. This case report describes an unusual presentation of a giant amelanotic malignant melanoma on the left hand, highlighting the diagnostic and management complexities. A 45-year-old male presented to the surgical oncology clinic with a three-year history of a progressively enlarging lump on his left hand. Initially small, the lesion rapidly grew in the past year, accompanied by ulceration and bleeding. Physical examination revealed an 8 cm x 6 cm x 4 cm rough-shaped, skin-colored mass with crusting and easily bleeding sores on the left palm. No axillary lymphadenopathy was noted. Histopathological examination of a biopsy sample indicated amelanotic malignant melanoma, which was confirmed by positive HMB-45 staining on immunohistochemistry. Magnetic Resonance Imaging (MRI) revealed a large soft tissue mass infiltrating the muscles of the left hand and causing bone marrow replacement in the 4th and 5th metacarpal bones. The patient subsequently underwent wrist disarticulation. Postoperative follow-up at one and six months showed good recovery without recurrence. In conclusion, this case underscores the importance of considering amelanotic melanoma in the differential diagnosis of unusual hand lesions, even in the absence of typical pigmentation. Proper histopathology and immunohistochemistry are crucial for accurate diagnosis and to rule out other malignancies. This report contributes to the limited literature on giant AAM of the hand and highlights the surgical management of this rare entity.